PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA “GELAS AJAIB” UNTUK MENINGKATKAN HASIL BELAJAR PERKALIAN BILANGAN CACAH SISWA KELAS IV - Dini Rahmatika; Linda Nur Aini; Putri Pramesti Hening; Wahyu Widiyatmoko (LPPM Universitas Cipta Mandiri, 2025)
The purpose of this study was to improve the learning outcomes of mathematics on the material of multiplication of numerical numbers in class IV through the application of the Problem Based Learning (PBL) model with the help of concrete media “Gelas Ajaib”. The method used is Classroom Action Research (PTK) with a two-cycle design, each of which consists of planning, implementation, observation, and reflection stages. The subjects of this study were students of class IV B in one of the private elementary schools in Surakarta totaling 19 people. This research approach used a mixed approach (quantitative and qualitative). The results showed an increase in students' learning outcomes from an average of 61.05 at the pre-cycle stage, to 63.95 in cycle I, and increased significantly to 73.95 in cycle II. The number of students who reached the Mastery Level Completion Criteria (KKTP) also increased from 15.78% in the pre-cycle to 36.84% in cycle I and 63.15% in cycle II. The novelty in this study lies in the integration of the PBL model with the “Magic Glass” media designed to facilitate understanding of the concept of multiplication concretely and contextually.